The renewable energy consumption-environmental degradation nexus in Top-10 polluted countries: Fresh insights from quantile-on-quantile regression approach - Sharif, Arshian; Mishra, Shekhar; Sinha, Avik; Jiao, Zhilun; Shahbaz, Muhammad; Afshan, Sahar (Elsevier Ltd., 2020)
This examination explored the link between renewable energy utilization and environmental degradation in top-10 polluted countries by using monthly data from 1990-2017. The Quantile-on-Quantile regression (QQ) proposed by Sim and Zhou (2015) and Granger causality in quantiles developed by Troster (2018) are applied. In particular, we examine in what manners, quantiles of renewable energy consumption affect the quantiles of environmental degradation. Our empirical findings unfold overall dependence between renewable energy consumption and ecological deterioration. The findings recommend the presence of a significant negative association between renewable energy consumption and environmental degradation in China, USA, Japan, Canada, Brazil, South Korea and Germany, predominantly in high and low tails but results are totally contrasting in the case of India, Russia and Indonesia. Furthermore, the outcomes of Granger-causality in quantiles conclude a bidirectional causal link between renewable energy consumption and environmental degradation. The empirical findings suggest that governments should need to subsidize green energy in declining ecological degradation.